Environmental factors influencing learner absenteeism in six schools in the Kavango Region, Namibia - Sanzila, Keith Mumba (Rhodes University, Faculty of Education, Department of Education, 2012)
This study on learner absenteeism takes place in the Namibian context with a focus on the Kavango region, located in Northern Namibia, where absenteeism has been identified as a problem. The intention of the study is to find out the relationship between learner absenteeism and environmental factors. The research question was framed as: How do environmental factors influence learner absenteeism in schools, conceptualised as human activity systems in the Kavango Region (Namibia)? The wider intention of this study is to inform processes that can be put in place to reduce the impact of environmental factors on learner absenteeism, with the ultimate view of improving the quality of education. The literature review provides insight into learner absenteeism in developing and developed nations. It outlines the Namibian policies developed for improving learner attendance and retention of learners in schools, with the view of improving access to school. The study is located within the broader goals of education of Namibia. The research adopts a qualitative interpretive approach, and focuses on environmental factors influencing learner absenteeism in six case studies, which are selected schools in the Kavango province. The study uses a variety of tools such as questionnaires, focus group interviews, observations and interviews as well as document analysis. It uses a combination of inductive and abductive modes of inference in the data analysis. It draws on systems thinking to develop a model that theorises the interrelated roles of different stakeholders, namely, learners, teachers, parents, educational officials (including the regional office and the Ministry of Education). It proposes possible strategies for reduction of learner absenteeism that could contribute towards the improvement of the quality of education. It also mentions the benefits of reducing learner absenteeism in the schools involved in the case study. The findings clearly show that poverty is the main environmental factor that influences learner attendance. The impact of poverty does not, however, occur in isolation; it interacts and has influence over other environmental factors such as alcohol abuse, sickness, lack of parental involvement, lack of motivation from stakeholders and household work. The study also found certain educational factors influenced learner absenteeism, such as teacher attitude, pedagogical styles, and lack of security. The study ends with recommendations to reduce learner absenteeism and recommendations for further research.
Keywords: School attendance -- Namibia -- Kavango; Education -- Namibia -- Kavango; Education and state -- Namibia -- Kavango; Education -- Social aspects -- Namibia -- Kavango; High school students -- Namibia -- Kavango -- Attitudes; High school students -- Namibia -- Kavango -- Social conditions